Jaminan dan Peningkatan Kualitas Dosen melalui Program Doktor pada PTKIN di Indonesia - Lailial Muhtifah; Sulaiman Sulaiman; Zaenuddin Zaenuddin (IAIN Sorong, 2018)
This research seeks to outline the importance of guarantees, and improve the quality of lecturers through the 5000 doctoral programs at the State Islamic Religious College (PTKIN) in Indonesia. Lecturers who hold doctoral degrees or who have S3 education qualifications are 2,498 lecturers or 19% percent of 12,819 lecturers. Data comes from the Ministry of Religion in the figures for 2016. Data analysis tools use exploratory data analysis (Exploratory Data Analysis - EDA). The 5000 doctoral program is a standard quality assurance criterion for prospective doctoral program students and quality standards for doctoral graduates.